Distinct Gut Microbiota Composition and Functional Category in Children With Cerebral Palsy and Epilepsy - Huang, Congfu; Li, Yinhu; Feng, Xin; Li, Dongfang; Li, Xiuyun; Ouyang, Qiuxing; Dai, Wenkui; Wu, Genfeng; Zhou, Qian; Wang, Peiqin; Zhou, Ke; Xu, Ximing; et al. (Frontiers in Pediatrics, 2019)
Cerebral palsy (CP) and epilepsy are two interactive neurological diseases, and their clinical treatment can cause severe side-effects to children's development, especially when it involves long-term administration of antiepileptic drugs. Accumulating studies on the gut-brain axis indicated that the gut microbiota (GM), which participates in various neurological diseases, would provide a harmless therapeutic target for the treatment of CP and epilepsy. To explore the GM characteristics in children with both CP and epilepsy (CPE), we collected fecal samples from 25 CPE patients (CPE group) and 21 healthy children (Healthy group) for 16S rDNA sequencing. In this study, we discovered significantly higher microbial diversity in CPE group as compared to healthy group (P<0.001). After selecting the top 15 most abundant genera in each group, we found significantly enriched Bifidobacterium, Streptococcus, Akkermansia, Enterococcus, Prevotella, Veillonella, Rothia, and Clostridium IV in the CPE group, and noticeably reduced Bacteroides, Faecalibacterium, Blautia, Ruminococcus, Roseburia, Anaerostipes, and Parasutterella. A GM co-occurrence network was also constructed, and negative correlations were discovered between Bacteroides and Lactobacillus (r=-0.768, P<0.001, FDR<0.001), as well as Intestinibacter and Bifidobacterium (r=-0.726, P<0.001, FDR<0.001). After KEGG annotation and functional enrichment, 24 functional categories exhibited different enrichment levels between the CPE and Healthy group. The functions associated with xenobiotics metabolism, immune system diseases, and neurodegenerative diseases were enriched in the CPE group. Conversely, the functional categories related to the biosynthesis of secondary metabolites were reduced. Furthermore, the neurodegenerative diseases were mainly attributed to Streptococcus, while an increased risk of immune system diseases was associated with enriched Akkermansia in the CPE patients. Generally, this study characterized the GM in CPE patients, illustrated the microbial co-occurrence relationships, and detected the functional distributions of the bacteria.